(untitled) (Journal of Hama University, 2025)
At recent years, studies have focused on magnetic suspension systems due to their important roles in industrial applications, such as carrying heavy metal objects of various shapes. Despite the many researches in the field of magnetic suspension systems, most of them were focused on exist a determined function transfer without explain its components effects. In this system, problems are arising to instability because the magnetic fields entangled with the target body will be variable according to the physical nature of the target body, and here it is necessary to resort to a control system through which a certain degree of stability can be ensured, sufficient to make the portable metal objects suspended in a stable position. For this purpose, an analytical study and a mathematical model of the magnetic levitation system was derived and an optimized INTEGRAL-LQR controller was designed to control the position. The analytical study of the electromagnetic system led to the determination of the electrical and mechanical parameters affecting the operation and stability of the system. Thanks to the use of INTEGRAL-LQR to control the position of the suspended body, it achieves a stable balance between the electromagnetic attraction force and the gravitational force of the suspended body.